Community awareness and risk of rabies associated with exposure to animals in India - N R Ramesh Masthi; T V Sanjay; S B Pradeep; H S Anwith (Wolters Kluwer Medknow Publications, 2019)
Background: Rabies is a fatal but preventable disease. Around the world, awareness studies about rabies have been widely used to understand the disease and in its preventive measures. Objectives: The present study was conducted to assess the awareness of rabies as a disease, its transmission, and prevention among the general population and also to assess the perceived health risks associated with exposure to animals. Methods: A cross-sectional study was undertaken across seven representative states in India between July and November 2017. Multistage sampling methodology was followed to select 1012 households as the primary sampling unit, and one adult responsible respondent from each household was interviewed as study participants. Results: Six hundred and eleven (60.4%) participants had heard of rabies. Only 0.2% had extensive knowledge of rabies. Majority (440, 72.0%) of the participants considered rabies as a fatal disease; 77.3% opined that risk of rabies from dogs was high compared to 41.6% who believed that there was little or no risk of rabies from cats. Only 37 (3.7%) participants were aware about preexposure prophylaxis. Conclusion: The awareness on rabies and its prevention in the study population was not satisfactory.